miR-20a regulates expression of the iron exporter ferroportin in lung cancer - Babu, Kamesh Rajendra; Muckenthaler, Martina (Journal of molecular medicine, 2016)
Ferroportin (FPN) exports iron from duodenal enterocytes, macrophages, and hepatocytes to maintain systemic iron homeostasis. In addition, FPN is expressed in various cancer cells. Here, we show that in lung cancer, FPN expression is regulated by miR-20a. Within the FPN-3′-untranslated region (3′UTR), we identify and experimentally validate three evolutionarily conserved target sites for the microRNA (miRNA) members of the miR-17 seed family, including miR-20a. Our analysis of RNA sequencing data from patients with lung adenocarcinoma (LUAD) and lung squamous cell carcinoma (LUSC) revealed that FPN messenger RNA (mRNA) levels are significantly decreased in tumor compared to matched healthy tissue, while miR-20a levels are increased. A significant negative correlation of miR-20a and FPN expression was observed. Functional studies further demonstrate that FPN is post-transcriptionally regulated by miR-20a in non-small cell lung cancer (NSCLC) cells and that overexpression or knockdown of miR-20a or FPN affects NSCLC proliferation and colony formation. Taken together, our data suggest that increased expression of miR-20 in lung cancer may decrease iron export, leading to intracellular iron retention, which, in turn, favors cell proliferation.